Structural and functional analysis of a conjugated bile salt hydrolase from Bifidobacterium longum reveals an evolutionary relationship with penicillin V acylase - Kumar, R. Suresh; Brannigan, James A.; Prabhune, Asmita; Pundle, Archana V.; Dodson, Guy G.; Dodson, Eleanor J.; Suresh, C. G. (Journal of Biological Chemistry, 2006)
Bile salt hydrolase (BSH) is an enzyme produced by the intestinal microflora that catalyzes the deconjugation of glycine- or taurine-linked bile salts. The crystal structure of BSH reported here from Bifidobacterium longum reveals that it is a member of N-terminal nucleophil hydrolase structural superfamily possessing the characteristic alpha beta beta alpha tetra-lamellar tertiary structure arrangement. Site-directed mutagenesis of the catalytic nucleophil residue, however, shows that it has no role in zymogen processing into its corresponding active form. Substrate specificity was studied using Michaelis-Menten and inhibition kinetics and fluorescence spectroscopy. These data were compared with the specificity profile of BSH from Clostridium perfrigens and pencillin V acylase from Bacillus sphaericus, for both of which the three-dimensional structures are available. Comparative analysis shows a gradation in activity toward common substrates, throwing light on a possible common route toward the evolution of pencillin V acylase and BSH.

Structural features of Penicillin acylase adsorption on APTES functionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
The immobilization of Penicillin acylase (PGA) enzyme (which belongs to the Ntn hydrolase super family) into the amino-functionalized SBA-15 mesoporous molecular sieve is carried out to see the effect of silica as a host matrix on the enzyme kinetics. Physicochemical characterization by nitrogen adsorption, powder XRD and TEM methods indicate that the characteristic hexagonal features and the original pore structure of the parent SBA-15 is retained even after the incorporation of PGA. The adsorption of PGA on SBA15 shows a dependence on the pore volume and the composition of the adsorbent. The maximum loading of the enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The trapped enzyme is more stable than the soluble form to temperature and pH environments and retained 73% of its activity after immobilization. This enhanced stability is attributed to the protective nature of the cage itself and to the rigidity of the SiO(2) matrix, which reduces the freedom of peptide-chain refolding of molecular motions that occur in denaturation processes. The strength of binding is very strong; however, the activity of the immobilized enzyme is then simply restored with very little leakage of enzyme from the support. An important feature of the immobilized PGA enzyme is the excellent reusability without significant loss in activity, which indicates potentially exciting industrial/biomedical application of this support. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Penicillin G acylase; PGA immobilized SBA-15; pH and temperatures stability; SBA-15

Silver nanoparticle studded porous polyethylene scaffolds: bacteria struggle to grow on them while mammalian cells thrive - D'Britto, Virginia; Kapse, Harsha; Babrekar, Harshada A.; Prabhune, Asmita; Bhoraskar, S. V.; Premnath, V.; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Silver nanoparticle studded scaffolds were prepared by exploiting the Ag+ ion reducing activity of sophorolipids-a class of `glycolipids' that cap the ensuing nanoparticles as well. To achieve this, the porous polyethylene scaffolds are subjected to N-2+H-2 plasma treatment, in the first step. Subsequently the sophorolipids are covalently attached to the amine groups on the polymer surface through simple amide chemistry to yield sophorolipid grafted polymer scaffolds. These are then exposed to Ag+ ions under appropriate conditions leading to the formation of silver nanoparticles immobilized on the polymer scaffolds. It has been found that while bacteria do not survive on these silver studded scaffolds, CHO-K1 cells thrive on them making them good candidates for tissue engineering and bio-implant applications.

Structural determination and chemical esterification of the sophorolipids produced by Candida bombicola grown on glucose and alpha-linolenic acid - Gupta, Reetika; Prabhune, Asmita (Biotechnology Letters, 2012)
The extracellular surface-active glycolipids produced by the yeast, Candida bombicola when grown on glucose and alpha-linolenic acid, were analyzed by HPLC with electro-spray ionization (ESI-MS) and collision-induced dissociation mass spectrometry. The analysis confirmed that the sophorolipid (SL) mixture contained three different forms of C18:3 SL molecules: free acid, lactone and a diacetylated lactone, which has not been reported previously. Also a minor amount of diacetylated lactone form of C18:1 SL was detected. Further, the SL mixture was subjected to chemical esterification reaction with sodium methoxide. The reaction product was analyzed with ESI-MS and confirmed to be the single homogenous esterified product containing C18:3 moieties in its fatty acid chain.
Keywords: Candida bombicola; Collision-induced dissociation mass spectrometry; Electrospray ionization mass spectrometry; HPLC; Linolenic acid; Sophorolipid methyl ester

Selective imaging of quorum sensing receptors in bacteria using fluorescent Au nanocluster probes surface functionalized with signal molecules - Mukherji, Ruchira; Samanta, Anupam; Illathvalappil, Rajith; Chowdhury, Somak; Prabhune, Asmita; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2013)
Fluorescent ultrasmall gold clusters decorated with bacterial quorum sensing signal molecules, acyl homoserine lactone, are synthesized. These fluorescent probes are found to have emission in the near-infrared spectral region advantageous for bioimaging. Imaging studies using different. strains of bacteria with and without acyl homoserine lactone receptors with the aid of confocal microscopy have shown that the probe interacts preferentially with cells possessing these receptors. This indicates that, with appropriate surface functionalization, the Au clusters can be used for receptor specific detection with enhanced selectivity.
Keywords: Au nanoclusters; Biosensor; fluorescence imaging; quorum sensing

Sophorolipid assisted tunable and rapid gelation of silk fibroin to form porous biomedical scaffolds - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (RSC Advances, 2015)
Three dimensional polymer hydrogels, based on both natural and synthetic polymers, are increasingly being used as scaffolds and drug delivery vehicles for biomedical applications. Fibrous protein, silk fibroin (SF), obtained from the Bombyx mori silkworm is a promising candidate in this area. However, SF has a long gelation time of about a few weeks that can only be reduced by non-physiological treatments (e. g. high temperature, ultrasonication and low pH) or by addition of a chemical and non-biodegradable polymer and/or surfactant. We report here accelerated gelation of SF under physiological conditions using a biosurfactant, sophorolipid (SL) as a gelling agent. SL and SF are completely miscible and form a very clear solution upon mixing. Hence it is interesting to see that this clear solution gels in a time span of just a few hours. The hydrogels so formed have pore architecture, porosities and mechanical stability ideally suited for tissue culture applications. Here we also demonstrate that mouse fibroblast cells not only adhere to but also extensively proliferate on these SF-SL scaffolds.

Silk fibroin-sophorolipid gelation: deciphering the underlying mechanism - Dubey, Parul; Kumar, Sugam; Aswal, Vinod K.; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Prabhune, Asmita; Nisal, Anuya (Biomacromolecules, 2016)
Silk fibroin (SF) protein, produced by silkworm Bombyx mori, is a promising biomaterial, while sophorolipid (SL) is an amphiphilic functional biosurfactant synthesized by nonpathogenic yeast Candida bombicola. SL is a mixture of two forms, acidic (ASL) and lactonic (LSL), which when added to SF results in accelerated gelation of silk fibroin. LSL is known to have multiple biological functionalities and hence hydrogels of these green molecules have promising applications in the biomedical sector. In this work, SANS, NMR, and rheology are employed to examine the assembling properties of individual and mixed SLs and their interactions with SF to understand the mechanism that leads to rapid gelation. SANS and NMR studies show that ASL assembles to form charged micelles, while LSL forms micellar assemblies and aggregates of a mass fractal nature. ASL and LSL together form larger mixed micelles, all of which interact differently with SF. It is shown that preferential binding of LSL to SF causes rapid unfolding of the SF chain leading to the formation of intermolecular beta sheets, which trigger fast gelation. Based on the observations, a mechanism for gelation of SF in the presence of different sophorolipids is proposed.

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.

Silk fibroin-sodium dodecyl sulfate gelation: molecular, structural, and rheological insights - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita; Nisal, Anuya; Ravindranathan, Sapna (Langmuir, 2019)
A gelling agent is necessary to accelerate sol to gel transition in an aqueous solution of silk fibroin (SF), which otherwise takes several days to complete. In this paper, we investigate the mechanism of gelation of Bornbyx mori SF by a model anionic surfactant, sodium dodecyl sulfate (SOS). Even though interactions between SDS and proteins have been extensively investigated, most of these studies have focused on globular proteins, which undergo denaturation. The interaction with a fibrous protein such as SF is different and results in an altered secondary structure leading to gelation. In this work, the concentration-dependent gelation process of the SF-SDS system is examined using rheology, SANS, FTIR, and NMR. We observed preferential binding of SDS to specific regions on the SF chain, which aids structural changes favoring beta-sheet formation. We propose a mechanism for the accelerated sol-gel transition in the SF-SDS system.

Structural and enzymatic analysis of a dimeric cholylglycine hydrolase like acylase active on N-acyl homoserine lactones - Philem, Pushparani D.; Yadav, Yashpal; Sunder, Avinash Vellore; Ghosh, Deepanjan; Prabhune, Asmita; Ramasamy, Sureshkumar (Biochimie, 2020)
The prevalence of substrate cross-reactivity between AHL acylases and beta-lactam acylases provides a glimpse of probable links between quorum sensing and antibiotic resistance in bacteria. Both these enzyme classes belong to the N-terminal nucleophile (Ntn)-hydrolase superfamily. Penicillin V acylases alongside bile salt hydrolases constitute the cholylglycine hydrolase (CGH) group of the Ntn-hydrolase superfamily. Here we report the ability of two acylases, Slac1 and Slac2, from the marine bacterium Shewanella loihica PV4 to hydrolyze AHLs. Three-dimensional structure of Slac1 reveals the conservation of the Ntn hydrolase fold and CGH active site, making it a unique CGH exclusively active on AHLs. Slac1homologs phylogenetically cluster separate from reported CGHs and AHL acylases, thereby representing a functionally distinct sub-class of CGH that might have evolved as an adaptation to the marine environment. We hypothesize that Slac1 could provide the structural framework for understanding this subclass, and further our understanding of the evolutionary link between AHL acylases and beta-lactam acylases. (C) 2020 Elsevier B.V. and Societe Francaise de Biochimie et Biologie Moleculaire (SFBBM). All rights reserved.
Keywords: AHL acylase; Cholyolglycine hydrolase; Homodimer; Ntn-fold; Shewanella loihica-PV4